Respostas
respondido por:
3
Ola Thiag
105 = 60 + 45
sen(60) = √3/2 , cos(60) = 1/2
sen(45) = √2/2 , cos(45) = √2/2
cos(a + b) = cos(a)*cos(b) - sen(a)*sen(b)
cos(60 + 45) = cos(60)*cos(45) - sen(60)*sen(45)
cos(60 + 45) = (1/2)*(√2/2) - (√3/2)*(√2/2)
cos(105) = (√2 - √6)/4
105 = 60 + 45
sen(60) = √3/2 , cos(60) = 1/2
sen(45) = √2/2 , cos(45) = √2/2
cos(a + b) = cos(a)*cos(b) - sen(a)*sen(b)
cos(60 + 45) = cos(60)*cos(45) - sen(60)*sen(45)
cos(60 + 45) = (1/2)*(√2/2) - (√3/2)*(√2/2)
cos(105) = (√2 - √6)/4
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás